Multidimensional Determinants of foreign Direct Investment in Central Africa: A Modified Gravity GMM Panel Approach - Ngouhouo, Ibrahim (Mediterranean Journal of Social Sciences, 2013)
This research's objective is to highlight the multidimensional determinants of FDI in Central Africa countries, especially in theEconomic and Monetary Community of Central Africa (EMCCA). To do this, a modified and adapted gravity model isconstructed and tested by the GMM method. The main result shows that natural resources are by far the most significantdeterminant of FDI in the EMCCA. Market size (population and gross domestic product) may also play a role in attracting FDIin addition to natural resources and infrastructure. However, we find that economic openness remains to be perfect to attractforeign investors.